2019
DOI: 10.1021/acs.jcim.8b00979
|View full text |Cite
|
Sign up to set email alerts
|

Using Graphs of Dynamic Hydrogen-Bond Networks To Dissect Conformational Coupling in a Protein Motor

Abstract: DExD/H-box proteins are soluble enzymes that couple binding and hydrolysis of adenosine triphosphate (ATP) with reactions involving RNA metabolism or bind and push newly synthesized proteins across bacterial cell membranes. Knowledge of the reaction mechanism of these enzymes could help the development of new therapeutics. In order to explore the mechanism of long-distance conformational coupling in SecA, the DEAD-box motor of the Sec protein secretion in bacteria, we implemented algorithms that provide simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…Previous MD simulations indicated that the residence times of waters largely depend on the location of the hydration site: waters in the convex regions of myoglobin were found to have short residence times of r10 ps, whereas waters trapped inside the protein or in groove regions could have residence times as long as B457 ps; 37 a qualitatively similar observation was made in recent computations of the SecA protein motor. 38 The upper value of water residence times obtained from MD simulations is compatible with Nuclear Magnetic Resonance (NMR) studies indicating a subnanosecond range for the residence times of water molecules on a protein surface. 39 To dissect dynamic interactions at the interface between PsbO and PsbU we analyzed the crystal structures of PSII, performed classical mechanical MD simulations, implemented a protocol to compute the residence times of waters interacting with PsbO and PsbU, and pursued extensive analysis of dynamic carboxylate-water H-bond networks.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous MD simulations indicated that the residence times of waters largely depend on the location of the hydration site: waters in the convex regions of myoglobin were found to have short residence times of r10 ps, whereas waters trapped inside the protein or in groove regions could have residence times as long as B457 ps; 37 a qualitatively similar observation was made in recent computations of the SecA protein motor. 38 The upper value of water residence times obtained from MD simulations is compatible with Nuclear Magnetic Resonance (NMR) studies indicating a subnanosecond range for the residence times of water molecules on a protein surface. 39 To dissect dynamic interactions at the interface between PsbO and PsbU we analyzed the crystal structures of PSII, performed classical mechanical MD simulations, implemented a protocol to compute the residence times of waters interacting with PsbO and PsbU, and pursued extensive analysis of dynamic carboxylate-water H-bond networks.…”
Section: Introductionsupporting
confidence: 77%
“…To estimate errors in C(t) we used block averaging. 68 The KWW stretched exponential from eqn (3) had been used to calculate the water residence times of water molecules interacting with proteins 38,65,69 and lipid bilayers. 63 Our initial test computations indicated that, for a relatively large number of sites of the PsbO-PsbU complex, the KWW exponential gives relatively poor fits of C(t); this result is compatible with previous observations.…”
Section: Residence Times Of Water In the First Hydration Shells Of Psmentioning
confidence: 99%
“…We further used 10 coordinate snapshots from a simulation on the soluble protein SecA ( Karathanou and Bondar, 2019 ) to calculate the total number of protein H-bonds with i) the combined criteria of ≤3.5 Å distance between heavy atoms and ≤60° H-bond angle; ii) the criterion of a ≤2.5 Å distance between the H atom and the heavy atom. We obtained for SecA a total of 220–236 H-bonds in test i) , and 223–240 H-bonds in test ii) , suggesting the combined 60° angle and 3.5 Å heavy-atom distance criterion is largely equivalent to using a distance of 2.5 Å between the heavy atom and the H atom.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained for SecA a total of 220–236 H-bonds in test i) , and 223–240 H-bonds in test ii) , suggesting the combined 60° angle and 3.5 Å heavy-atom distance criterion is largely equivalent to using a distance of 2.5 Å between the heavy atom and the H atom. In two additional tests on SecA simulations that start from two different protein conformations ( Karathanou and Bondar, 2019 ), we used the combined 3.5 Å distance and 60°-angle criterion to compute the frequency for all H-bonds present in starting crystal structures. We found that about 90–95% of H-bonds that appear as weak in a protein crystal structure, with the distance between the heavy atoms from 3.0 Å to 3.5 Å, are nevertheless sampled over the course of the two prolonged simulations, and almost 60–75% of the weak H-bonds are sampled during at least 10% of the two simulations.…”
Section: Methodsmentioning
confidence: 99%
“…Once we computed a protein's graph of hydrogen bonds, we can use centrality measures to identify protein groups that are common to hydrogen-bond paths of particular interest for the functioning of that protein (110). With betweenness centrality, for example, we evaluate how often a protein group participates in short-distance paths that connect any two other protein groups (110). Such an analysis revealed that, on the surface of photosystem II, there is a carboxylate group (PsbU-E93 in (Fig.…”
Section: Long-distance Proton Transfers Via Dynamic Hydrogen-bond Netmentioning
confidence: 99%